Lactobacillus Rhamnosus GG Role in the Suppression of Candida Albicans Causing Candidiasis (Thrush) - Rahem Alziadi; Nuha Mohammed Mousa; Noor Sami AL- Lebawy (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: It is important to distinguish infecting strains of Candida albicans because isolates of Candidaspecies vary widely, both in their infection-causing capacity and in their sensitivity to antifungal agents.Material and method: Thus this study provides isolate candida and identification of isolates from the oralcavity and test the antimicrobial activity of Lactobacillus rhamnosus GG and their supernatants on theviability of Candida albicans isolates. The diagnosis was based on conventional methods, and geneticdiagnosis was confirmed by PLC1 gene (PhosphoLipase C) amplification, the design primers were done byusing the database of Bank of NCBI-Gene and online design, all isolates gives positive PCR products withmolecular weight 459bp,Result: The results showed that Lactobacillus rhamnosus GG and their supernatants decreased the logcycles growth of all Candida albicans isolates with average (1.7 -2.1) logarithmic cycle for live cells and(1.28 -1.79) logarithmic cycle for Lactobacillus rhamnosus GG supernatants, Conclusion: Lactobacillusrhamnosus GG may be a suitable and effective alternative to treatment oral candidiasis free from side effects.